Anaplastic lymphoma kinase (ALK) gene alteration in signet ring cell carcinoma of the gastrointestinal tract. (March 2015) - Alese, Olatunji B.; El-Rayes, Bassel F.; Sica, Gabriel; Zhang, Guojing; Alexis, Dianne; La Rosa, Francisco G.; Varella-Garcia, Marileila; Chen, Zhengjia; Rossi, Michael R.; Adsay, Nazim V.; Khuri, Fadlo R.; Owonikoko, Taofeek K.
Objectives: ALK-EML4 translocation is an established driver aberration in non-small cell lung cancer (NSCLC), with reported predilection for cases with signet ring histology. We assessed the presence of anaplastic lymphoma kinase (ALK) gene rearrangements in signet ring cancers arising in the stomach and colon. Methods: Histologically confirmed cases of signet ring adenocarcinoma of the stomach or the colon were identified. The presence of the classic ALK and EML4 fusion gene was initially determined by fluorescence in-situ hybridization (FISH) technique. Immunohistochemistry (IHC) was performed using two previously validated antibodies, ALK1 clone (1:100; DAKO) and 5A4 (Novocastra, Leica Biosystems) along with positive controls of ALK-translocated lung cancer. Results: We employed 42 cases of signet ring carcinoma diagnosed between 2001 and 2011; 25 gastric and 17 colon cancer. Median age 63.3 years; male/female 17/25; race, black 47.5%, white 47.5%, others, 5%; stage I, 21.4%; stage II, 31%; stage III, 26.2%; stage IV, 21.4%. One of 42 cases (2.3%) was positive for ALK translocation by FISH using the standard criteria of at least 15% positive cells for the break-apart signal (50–70 cells enumerated per case). Using a less restrictive cut-off of 10% positive cells, 7 cases (16%) were considered possibly positive. None of the 'possibly positive' cases was found to harbor ALK translocation by another molecular testing approach (IHC). IHC with two previously validated monoclonal antibodies showed 0 of 42 (0%) cases positive. Conclusions: ALK gene rearrangement is very rare in gastrointestinal cancers and enrichment strategy focusing on signet ring cell histology did not significantly improve the detection rate.